Prevalence and Associated Factors of Age-Related Macular Degeneration in a Russian Population: The Ural Eye and Medical Study - Bikbov, Mukharram M.; Zainullin, Rinat M.; Gilmanshin, Timur R.; Kazakbaeva, Gyulli M.; Rakhimova, Ellina M.; Rusakova, Iulia A.; Bolshakova, Natalia I.; Safiullina, Kamilla R.; Yakupova, Dilya F.; Uzianbaeva, Yulia V.; Khalimov, Timur A.; Salavatova, Venera F.; et al. (American journal of ophthalmology, 2020)
To assess the prevalence of age-related macular degeneration (AMD) in a Russian population. Population-based prevalence assessment. The Ural Eye and Medical Study was conducted in a rural and urban area in the Russian republic of Bashkortostan. The study included 5,899 participants aged 40+ years old. AMD, defined according to the Beckman Initiative for Macular Research, was assessed by fundus photographs and optical coherence tomographic images of 4,932 (83.6%) participants. The prevalence of any AMD, early AMD, intermediate AMD, or late AMD, geographic atrophy, and neovascular AMD were 18.2% (95% confidence interval [CI], 16.8-19.6), 11.6% (95% CI, 10.4-12.8), 5.0% (95% CI, 4.2-5.8), 1.6% (95% CI, 1.1-2.0), 0.7% (95% CI, 0.4-1.0) and 0.9% (95% CI, 0.6-1.3), respectively, for individuals >55 years old. Applying an age limit of 40+ years for the AMD definition, prevalence of any AMD, early AMD, intermediate AMD, late AMD, geographic atrophy and neovascular AMD were 14.1% (95% CI, 13.1-15.1), 9.4% (95% CI, 8.6-10.2), 3.8% (95% CI, 3.2-4.3), 1.0% (95% CI, 0.7-1.2), 0.4% (95% CI, 0.2-0.6) and 0.5% (95% CI, 0.3-0.7), respectively, for individuals aged 40+ years. Higher AMD prevalence was correlated with older age (odds ratio [OR], 1.15; 95% CI, 1.13-1.16; P < 0.001), rural region (OR, 1.69; 95% CI, 1.32-2.17; P < 0.001), lower diabetes prevalence (OR, 0.56; 95% CI, 0.38-0.82; P = 0.003), and shorter axial length (OR, 0.89; 95% CI, 0.79-0.99; P = 0.04). AMD prevalence was not significantly (all P ≥ 0.20) correlated with any systemic parameter examined, except for lower prevalence of diabetes. In this typical, ethnically mixed, urban and rural population from Russia, a higher prevalence for AMD was associated mainly with older age, rural region of habitation, shorter axial length, and lower prevalence of diabetes mellitus. The AMD prevalence was lower than in Europeans and higher than in East Asians.